TikTok as a Media to Enhancing the Speaking Skills of EFL Student's - Zaitun Zaitun; Muhammad Sofian Hadi; Emma Dwi Indriani (Jurnal Studi Guru dan Pembelajaran, 2021)
At this time, the world is facing a problem, namely fighting the Covid-19 virus. With a situation that causes everything to be done at home, including studying. And it becomes a challenge for teachers to be able to convey material appropriately online. And the TikTok application is very widely used by users, especially students, to upload related daily activities. Therefore, it is necessary to have new variations in the application of interactive and effective learning media in order to influence student learning motivation. This study aims to determine the improvement of students' speaking skills by storytelling about a person, object or place that you want to describe using the TikTok application. The subjects in this study were 36 students of class VIII H SMP Negeri 164 Jakarta. The method used is descriptive qualitative method using classroom action research techniques. The researcher conducted 1 session for the Pre-Test and 2 sessions for the Post-Test. The results showed that using the TikTok application as a medium for speaking students could increase students' confidence in speaking English and also added new experiences for students in expressing their ideas freely on TikTok. From the results of the Pre-Test session, there were 15 students who scored between 30-40. And the remaining 21 students got a score above 60. While in the post-test session 1 there was an increase with a total of 22 students getting a score above 70. Then in the post-test session 2 showed a very significant increase with the achievement of the highest student scores of 95 and the lowest of 70.